Investigation of Biochemical Effect of Phenols Extract Isolated from Coriandrum sativum Seeds Against Echinococcus granulosus Parasite in Vitro - Abbas Dawwas (University of Thi-Qar Journal of Science, 2019)
This study was carried out to investigate effect of phenols extract isolatedfrom Coriandrum sativum seeds extract against Echinococcus granulosus parasitegotten from livers of sheep infected by hydatid disease in Basrah abattoir . It wasfound that increase of concentration of extract led to decrease of protoscolicesviability and the number of dead protoscolices increased with increase of days .Also the concentration of (0.75 gm/ml) had the higher effect on viability ofprotoscolices where it was noticed that this concentration killed all protoscolicesafter three days of treatment wheras the concentration of (0.25 gm/ml) was theless effect where it led to kill protoscolices after seven days of treatment withextract . The viability percentage reached to zero at concentration of (0.75gm/ml) in the third day but at concentrations (0.5 and 0.6 gm/ml) was zero in thefourth day . Also it was found that protoscolices viability percentage was zero inthe seventh day of treatment by using concentration of (0.25 gm/ml) . Thereforephenols extract concentration of (0.75 gm/ml) can be used as a medicinal herbalsubstitute instead of antibiotics but it needs further clinical studies .